2018
DOI: 10.5483/bmbrep.2018.51.12.248
|View full text |Cite
|
Sign up to set email alerts
|

Tat-ATOX1 inhibits inflammatory responses via regulation of MAPK and NF-κB pathways

Abstract: Antioxidant 1 (ATOX1) protein has been reported to exhibit various protective functions, including antioxidant and chaperone. However, the effects of ATOX1 on the inflammatory response has not been fully elucidated. Thus, we prepared cell permeable Tat-ATOX1 and studied the effects on lipopolysaccharide (LPS)- and 12-O-tetradecanoyl phorbol-13-acetate (TPA)-induced inflammation. Experimental results showed that transduced Tat-ATOX1 protein significantly suppressed LPS-induced intracellular reactive oxygen spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…These results indicate that PEP-1-GLRX1 plays an anti-inflammatory role in TPA-induced skin inflammation. We have demonstrated that cell-permeable antioxidant PTD-fusion protein markedly inhibits TPA-induced inflammation in a mice model (27,48). In addition, other studies have reported that antioxidant proteins play protective roles in inflammation (51,52).…”
Section: Effect Of Pep-1-glrx1 On Mouse-ear Edemamentioning
confidence: 77%
See 4 more Smart Citations
“…These results indicate that PEP-1-GLRX1 plays an anti-inflammatory role in TPA-induced skin inflammation. We have demonstrated that cell-permeable antioxidant PTD-fusion protein markedly inhibits TPA-induced inflammation in a mice model (27,48). In addition, other studies have reported that antioxidant proteins play protective roles in inflammation (51,52).…”
Section: Effect Of Pep-1-glrx1 On Mouse-ear Edemamentioning
confidence: 77%
“…Since protein transduction is important for the development of therapeutic proteins, PTD-fused protein transduction can be used for the intracellular application of therapeutic proteins (20)(21)(22)(23)(24). In previous studies, we have demonstrated that PTD-fusion proteins were transduced into various cells (25)(26)(27)(28)(29)(30). In this study, we first identified the distribution of transduced PEP-1-GLRX1 using fluorescence analysis.…”
Section: Effect Of Pep-1-glrx1 On Expression Of Cox-2 and Inosmentioning
confidence: 99%
See 3 more Smart Citations